Cord Blood Thyroid Hormones and Neurodevelopment in 2-Year-Old Boys and Girls - Fan, Pianpian; Chen, Yuanzhi; Luo, Zhong-Cheng; Shen, Lixiao; Wang, Weiye; Liu, Zhiwei; Zhang, Jun; Ouyang, Fengxiu (Frontiers in Nutrition, 2021)
Objectives: Thyroid hormones are essential for neurodevelopment in early life. However, the impact of mild alterations in neonatal thyroid hormones on infant neurodevelopment and its sex-dimorphism is unclear. We aimed to assess whether mild variations in neonatal thyroid hormones of euthyroid mother are related to neurodevelopment in 2-year-old boys and girls. Methods: This study used data from 452 singleton term-born infants of mothers with normal thyroid function in Shanghai, China, and their follow-up measure at age 2 years. Cord serum concentrations of free triiodothyronine (FT3), free thyroxine (FT4), thyroid stimulating hormone (TSH), and thyroid peroxidase antibody (TPOAb) were measured by chemiluminescent microparticle immunoassays, and classified into three groups: the low (1st, Q1), middle (2nd-4th, Q2-Q4), and high (5th, Q5) quintiles. The neurodevelopment indices were assessed by Ages & Stages Questionnaire, third edition (ASQ-3) at age 24 months. Results: Compared to infants with thyroid hormones in the middle(Q2-Q4), boys with FT4 in the lowest quintile had 5.08 (95%CI: 1.37,8.78) points lower scores in communication, 3.25 (0.25,6.25) points lower scores in fine motor, and 3.84 (0.04, 7.64) points lower scores in personal-social domains, respectively. Boys with FT3 in the highest quintile had 4.48 (0.83,8.14) points increases in personal-social domain. These associations were not statistically significant in girls. Conclusions: Mild alterations in thyroid hormones of newborns were associated adversely with neurodevelopment in boys, suggesting the importance of optimal thyroid hormones status for neurodevelopment in early life.